The market economy and the human right to water in Africa - Branco, Manuel (2013)
Water being essential to human survival and, thus, a human right, why is there such inequality in its distribution? This inequality represents a serious violation of a human right, as it will be developed in the paper and therefore should not be tolerated. The main issue this paper wishes to address concerns the inability of the market in providing everyone access to clean water. More specifically, this paper will examine how the market discourse can be conflictive with the right to water. First of all, with the market satisfying wants implies the use of concepts like prices, supply and demand, or cost and benefit, and therefore, the issue is ability to pay, in other words purchasing power. With rights, on the other hand, the issue is quite different; the heart of the matter here concerns entitlement, the criteria according to which an individual should qualify to enjoy rights, purchasing power being obviously excluded as well as the consequences of the use of such criteria. Therefore it is perfectly admissible for economics to exclude from access to water those that do not have the capability to pay violating the basic principles of human rights. Second, market hegemony also hinders the human right to water because on one hand the market is inefficient in reaching universal coverage of water supply and on the other hand it is an unaccountable institution and human rights purveyors need by principle to be submitted to democratic control. Third, the lower the level of development measured by international standards, the lower is the power of the state in supplying basic goods, in regulating the markets and in guaranteeing a full coverage of safe water. This is the situation of many African countries, which requires specific policies in order to guarantee a minimum satisfaction of basic human rights, in particular water supply.